Why we can't sleep ebook Women's new midlife crisis. - Calhoun, Ada (2023)
The acclaimed author explores the hidden crises of Gen X women in this "engaging hybrid of first-person confession, reportage [and] pop culture analysis" ( The New Republic ). Ada Calhoun was married with children and a good career—and yet she was miserable. She thought she had no right to complain until she realized how many other Generation X women felt the same way. What could be behind this troubling trend? To find out, Calhoun delved into housing costs, HR trends, credit card debt averages, and divorce data. At every turn, she saw that Gen X women were facing new problems as they entered middle age—problems that were being largely overlooked. Calhoun spoke with women across America who were part of the generation raised to "have it all." She found that most were exhausted, terrified about money, under-employed, and overwhelmed. And instead of being heard, they were being told to lean in, take "me-time," or make a chore chart to get their lives and homes in order. In Why We Can't Sleep , Calhoun opens up the cultural and political contexts of Gen X's predicament. She offers practical advice on how to ourselves out of the abyss—and keep the next generation of women from falling in. The result is reassuring, empowering, and essential reading for all middle-aged women, and anyone who hopes to understand them.